Analisis Pengaruh Faktor Fundamental Terhadap Harga Saham (Studi pada Perusahaan Sektor Properti di Asia Tenggara Tahun 2008-2012 - Adi Irawan Setiyanto; Arfan Hadi (Politeknik Negeri Batam, 2014)
Generally, there are two approaches that are often used by investors to analyze and assess stocks in the capital market, fundamental analysis and technical analysis, but this time investors tend to only use analysis techniques in analyzing and selecting stocks. To prove that the fundamental factors also affect the stock price then filed this research. The data used are taken from the financial statements of the open company in 2008 until 2012. Population who want to observe is that companies in the property sector and has been listed on the Stock Exchange countries ASEAN member countries are taken through the site www.bloomberg.com. Appropriate sample to be tested 80 companies. Dependent variable in this study is a stock price that has been converted (PK) and the independent variables include the Earning Per Share has been converted (EPSK), Net Profit Margin (NPM), Return on Equity (ROE), Return on Assets (ROA) and debt to Equity Ratio (DER). Method is used is panel data regression method. The results showed in Indonesia, the fundamental factors that significantly affect the stock price is Earning per Share (EPSK) that has been converted. Malaysia, the fundamental factors that significantly affect the stock price is Net Profit Margin (NPM). Singapore, the fundamental factors that significantly affect the stock price is a net profit margin (NPM). Thailand, the fundamental factors that significantly affect the stock price is Return on Assets (ROA). Philippines, no significant fundamental factors that affect the stock price.